Cooperative regulation of electrical and thermal transport behavior enhancing the thermoelectric performance of SnTe. (November 2021) - Cui, Bo; Sun, Yuxin; Jiang, Yiyue; Shi, Wenjing; Zhou, Xiaosong; Peng, Shuming; Cai, Wei; Guo, Fengkai; Sui, Jiehe
Abstract: SnTe is a kind of promising candidates for medium temperature thermoelectric materials, while its thermoelectric properties are limited by not only the poor electrical transport properties caused by intrinsic high carrier concentration and large valence bands offset, but also the relatively high lattice thermal conductivity. In this work, the thermoelectric performance of Mn–Bi and Mn–Sb co-doped SnTe is investigated. As expected, Mn doping decreases the energy separation between the two valence band maxima, enabling improved Seebeck coefficient, the donor effect of Bi or Sb weakens the adverse effect of Mn doping on carrier concentration, and then a relatively high average power factor is achieved. More importantly, a variety of defects, including point defects, dislocations and nanoprecipitates, are introduced, which can scatter phonons in a wide frequency range and decrease the lattice thermal conductivity. Finally, the synergy of these effects yields a maximum ZT of 1.14 at 873 K and an average ZT of 0.7 (300–873 K) in Sn0·88 Bi0·04 Mn0·08 Te sample, and a maximum ZT of 1.23 at 873 K and an average ZT of 0.73 (300–873 K) in Sn0·82 Sb0·06 Mn0·12 Te sample. Graphical abstract: Image 1 Highlights: Mn–Bi co-doping with ratio of 2:1 keep the carrier concentration almost unchanged. Lots of dislocations and nano-precipitates are introduced in Mn–Sb co-doped SnTe. Average power factor and figure of merit are both improved by Mn–Bi(Sb) co-doping.